Eco‐friendly extraction and physicochemical properties of pectin from jackfruit peel waste with subcritical water - Li, Wen‐Jia; Fan, Zhi‐Guo; Wu, Ying‐Ying; Jiang, Zhi‐Guo; Shi, Rui‐Cheng (Journal of the science of food and agriculture, 2019)
BACKGROUND Water is generally considered to be a safe and green solvent suitable for use in natural product extraction. In this study, an eco‐friendly subcritical water method was used to extract pectin from waste jackfruit peel (JFP‐S), which was compared with pectin obtained by the traditional citric acid method (JFP‐C). RESULTS The extraction process was optimized using response surface methodology (RSM), and the optimum process parameters were as follows: extraction temperature 138 °C, extraction time 9.15 min, liquid / solid (L/S) ratio 17.03 mL g−1. Under these conditions, the pectin yield was 149.6 g kg−1 (dry basis). Pectin obtained from the two extraction methods displayed a high degree of esterification and the monosaccharide composition was consistent. The galacturonic acid content of JFP‐S and JFP‐C was 52.27% and 56.99%, respectively. JFP‐S had more hairy regions and side chains than JFP‐C. The molecular weight of JFP‐S was 113.3 kDa, which was significantly lower than that of JFP‐C (174.3 kDa). Fourier‐transform infrared spectroscopy (FTIR) indicated that two samples had similar pectin typical absorption peaks. According to differential scanning calorimetry (DSC), both JFP‐S and JFP‐C had relatively good thermal stability. JFP‐S demonstrated lower apparent viscosity and elasticity than JFP‐C. Meanwhile, the G′ and G′′ moduli of JFP‐S were lower, which found expression in the gel textural characterization of the samples. CONCLUSION This work showed that the subcritical water method is an efficient, time‐saving, and eco‐friendly technology for the extraction of pectin from jackfruit peel compared with the traditional citric acid method. The physicochemical properties of pectin could be changed during subcritical water extraction. © 2019 Society of Chemical Industry